2005
DOI: 10.1111/j.1551-2916.2005.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Magnetic Properties of Novel Yttria‐Stabilized Tetragonal Zirconia/Ni Nanocomposite Prepared by the Modified Internal Reduction Method

Abstract: Dense ceramic/metal nanocomposite has been fabricated by internal reduction method, which includes a two‐step process: sintering of ceramic–metal oxide solid solution and subsequent heat treatment in a reducing atmosphere to precipitate metal nanoparticles. This novel technique has been applied to yttria‐stabilized tetragonal zirconia (Y‐TZP) and nickel oxide (NiO) system to fabricate Y‐TZP/Ni nanocomposite. Dense Y‐TZP and 0.3 mol% NiO solid solution ceramic was successively prepared by the pressureless sinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
(114 reference statements)
0
21
0
Order By: Relevance
“…1 Nanocomposite materials have been extensively explored for many technological applications due to specific combinations of mechanical, optical, catalytic, electrical or magnetic properties with fundamentally different properties that cannot be achieved for single phase, pure materials. [2][3][4] Ceramic-metal nanocomposites are promising candidate materials for fabricating multifunctional nanodevices due to sometimes outstanding electrical properties with very particular features. 5,6 In order to realize an optimized microstructure for ceramic-metal nanocomposites, much effort has been undertaken concerning the control of the size and distribution of the metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…1 Nanocomposite materials have been extensively explored for many technological applications due to specific combinations of mechanical, optical, catalytic, electrical or magnetic properties with fundamentally different properties that cannot be achieved for single phase, pure materials. [2][3][4] Ceramic-metal nanocomposites are promising candidate materials for fabricating multifunctional nanodevices due to sometimes outstanding electrical properties with very particular features. 5,6 In order to realize an optimized microstructure for ceramic-metal nanocomposites, much effort has been undertaken concerning the control of the size and distribution of the metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersion of nanoscale particles into the ceramic matrix is used to improve the mechanical properties of a ceramic‐based nanocomposite system. The incorporation of nanoparticles in the ceramics matrix facilitates considerable modification of the behavior of the ceramics, which exposes new functions such as superplasticity or high machinability like metal 17 …”
Section: Introductionmentioning
confidence: 99%
“…It was shown that inclusions of nanoscale secondary metallic phases into ceramic matrices have beneficial effects on both hardness and toughness of zirconia [14,15] and alumina [16]. An extensive review on ceramic/metal micro-and nanocomposites is presented by Moya [17].…”
Section: Introductionmentioning
confidence: 98%